Methodological proposal for the ambulatory detection of covid-19 symptoms, using low-cost devices - Auccahuasi, Wilver (2020)
ABSTRACT The pandemic caused by COVID-19, allowed to know at many levels, the situation of hospitals and its impact on the services they provide to the population. At the times with the highest rate of infections, health centers in most countries were brought to their maximum capacity, most of them collapsing and ceasing to attend to patients. Many health centers were dedicated only to treating patients infected by COVID-19. Lacking medical attention to the other specialties. In this environment, many of the symptomatic patients, such as asymptomatic ones, did not know if they had been infected, much less, did not know if they were infected, many of them were unable to detect certain symptoms so that they could request specialized medical attention. This work is dedicated to using low-cost devices as an evaluation and alert mechanism for possible symptoms caused by COVID-19, the methodology is based on the analysis of heart rhythm, blood pressure and oxygen saturation, the latter is the most important, because if the oxygen saturation begins to decrease, it is a symptom that the airways are being affected, which could be complicated if the oxygen saturation has a tendency to decrease, the variation of the rhythm can also be analyzed heart rate and blood pressure, but the predominant one is Oxygen Saturation. The results show that wearable devices in the form of a watch are widely used to control people's movements, the exercises they perform, the proposed methodology consists of a device that has the ability to evaluate these three biomedical variables, it is not necessarily a medical device with a high degree of sensitivity or accuracy. The usefulness of the device is to be able to carry out a quick analysis that helps people make a decision, the technique is not to measure oxygen saturation with a high degree of accuracy, the idea is to be able to measure if the saturation has a tendency to decrease. In the results we present the measurement of several people to verify the methodology.